2021
DOI: 10.3389/fpubh.2021.716483
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Seroprevalence and Profiles Among Convalescents in Sichuan Province, China

Abstract: Objectives: To explore and understand the SARS-CoV-2 seroprevalence of convalescents, the association between antibody levels and demographic factors, and the seroepidemiology of convalescents of COVID-19 till March 2021.Methods: We recruited 517 voluntary COVID-19 convalescents in Sichuan Province and collected 1,707 serum samples till March 2021. Then we reported the seroprevalence and analyzed the associated factors.Results: Recent travel history was associated with IgM levels. Convalescents who had recent … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…For this purpose, different investigations have conducted several seroepidemiological surveys worldwide to measure the seroprevalence of antibodies against SARS-CoV-2 [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. These studies have demonstrated the importance of the humoral immune response for the elimination of viral infection, and the important role of understanding the dynamics of antibodies against SARS-CoV-2, which help not only in assessing immunological levels and predicting potential immune protection, but also in the development of vaccine and immune therapy strategies [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, different investigations have conducted several seroepidemiological surveys worldwide to measure the seroprevalence of antibodies against SARS-CoV-2 [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. These studies have demonstrated the importance of the humoral immune response for the elimination of viral infection, and the important role of understanding the dynamics of antibodies against SARS-CoV-2, which help not only in assessing immunological levels and predicting potential immune protection, but also in the development of vaccine and immune therapy strategies [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are roles -albeit with some limitations-for the use of antibody testing. Currently, these tests are commonly used as a tool for seroprevalence studies [19][20][21], contributing to the understanding of the immune response to the virus [22]. Even with the advent of vaccines, depending on the vaccine platform used, antibody testing can also be used to distinguish between vaccinated and non-vaccinated individuals [23][24][25].…”
Section: Introductionmentioning
confidence: 99%